Health Care Engagement Behaviors of Men who Use Performance- and Image-Enhancing Drugs in Australia. Issue 1 (January 2020) - Jacka, B.; Larance, B.; Copeland, J.; Burns, L.; Farrell, M.; Jackson, E.; Degenhardt, L.
Background: Although people who inject performance- and image-enhancing drugs (PIEDs) report fewer unsafe injecting practices, stigma and discrimination may negatively impact their access to help and information. Engagement with health care services, compared with social networks (friends, relatives, and gym associates) and the Internet and media (steroid user forums, information sites, and magazines), may be important for harm minimization. Methods: A cross-sectional Internet or in-person survey of men who use PIEDs in Australia in 2014–2015 examined differences in sources for PIEDs, injecting equipment, and anabolic-androgenic steroids (AAS) information and factors associated with having periodical medical checks related to PIEDs issues using multivariate logistic regression. Results: In total, 267 men (mean age: 25 years, SD: 8.7 years; 246 of 267 [92%] reported recent AAS injection) were recruited. Most participants sourced injecting equipment from health professionals, PIEDs from their social networks, and AAS information from the Internet and media. Self-reported AAS knowledge was high and frequent. Higher income (adjusted odds ratio [AOR]: 2.04, 95% confidence interval [CI]: 1.03, 4.00), ≥2 different PIEDs used in addition to AAS (AOR: 1.94, 95% CI: 1.08, 3.49), and sourcing AAS information from health care professionals (AOR: 3.14, 95% CI: 1.81, 5.46) were independently associated with periodical medical checks. Participants nominated preference for improved health services through needle-syringe programs, primary care services, and peer educator support groups. Conclusion: Men who use PIEDs in Australia consider themselves well informed but tend to use Internet and media sources, providing potentially misleading or inaccurate information. Increasing trust between men who use PIEDs and health care providers may enable delivery of PIEDs-specific information to those at greatest need.